La Monetización del Selfie en las culturas participativas: Una aproximación transdisciplinaria a campañas publicitarias globales en el 2014 - Fonseca González, Vanessa (2021)
This article discusses how advertising appropriates selfies into creative strategies. From a visual studies perspective, it highlights how today particular visual regimes, such as selfie culture, on one hand promote products and brands as innovative, authentic or disruptive while, on the other, also convey individuality and privacy as evidence of transparency and authenticity. In participatory cultures, selfies become a commodity, in symbolic and economic terms. More than images, selfies are quantified data that can provide important tracking information over audiences and consumers through social media. First, visual studies help to evidence how advertising capitalizes from selfie culture through a commodification process. Second, from a critical perspective, it also addresses how advertising uses it to build brand positioning, individuality or a collective sense of belonging to our planet. Selfies’ exchange value and immeadicy are simultaneously commodified and aestheticized by using high culture cues, consumption practices and brand strategies. Dove’s digital strategies in 2014 worth mentioning since consumers’ selfies become data and revenue in digital, participatory cultures. Finally, the article discussess some relevant fundraising campaigns that chose selfie production as a basis to disseminate their ideas and goals for social good. Keywords: selfie; advertising; monetization; visual studies, branding.